Bad Apps: mHealth Apps Doubling as Medical Devices. Issue 4 (1st October 2016) - Herron, Jennifer
ABSTRACT: Smartphones and mobile devices are a common sight to see today and this rise in use has garnered an abundance of apps, known as mHealth apps, aimed to help consumers manage their health. While some apps have been found to be useful, such as fitness trackers, logs and diaries, others have been found to potentially be harmful. These potentially harmful apps pose as alternatives to medical devices and lead consumers to believe that they function just as accurately. Healthcare professionals and consumers both need to become more aware of mHealth apps and the different functions they serve so they may better be able to avoid potentially harmful apps.